Antecedents of social commerce purchase intention: evidence from Tanzanian social media users - Goodluck Charles; Renger Kanani (Cogent Business & Management)
While social commerce is developing as a relatively new stream in e-commerce that combines commercial and social activities, there is limited evidence regarding the social commerce environment and consumers’ purchase intention. For the purpose of contributing knowledge to this area, this study examined the antecedents of social commerce purchase intention by social media users in Tanzania. Based on online and offline surveys of 155 social media users and regression results, the study indicates that information richness, service quality, webpage attractiveness, and offline word of mouth positively influenced social commerce consumers’ purchase intention. Using the necessary condition logic to rank the factors identified, the offline recommendation quality was observed to be the most critical factor, followed by service quality, webpage attractiveness, and information richness. However, while the age of the post was significant in the regression model, it was insignificant in the necessary condition test. Accordingly, this study contributes knowledge by showing the drivers of social commerce consumer behavior in the context of a developing economy where social commerce is still at the nascent stage. It shows how the perspectives of signaling and social influence are integrated in online commercial and social interactions.